Clinical and radiographic outcomes of autologous pulp transplantation enhanced with concentrated growth factor in mature necrotic teeth: a clinical study - Kamalak, Aliye; Balkanlıoğlu, Esra; Tatar, Elife Ülkü (Vojnosanitetski pregled, 2026)
Background/Aim. Regenerative endodontic therapy in mature teeth remains challenging due to limited stem cell recruitment and apical vascularization. The aim of the prospective pilot clinical study was to evaluate the feasibility and preliminary clinical, radiographic, and functional outcomes of autologous pulp transplantation enhanced with concentrated growth factor (CGF) in mature necrotic permanent teeth. Methods. The study included six systemically healthy patients (five females and one male, aged 18–27 years) presenting with single-rooted mature permanent teeth, diagnosed with pulp necrosis and associated periapical lesions. Autologous pulp tissue was harvested from extracted third molars and transplanted into disinfected recipient root canals in combination with CGF prepared from venous blood. Clinical and radiographic evaluations were performed at 3, 6, and 12 months. Periapical healing was assessed using cone-beam computed tomography (CBCT), while pulp sensibility was evaluated using electric pulp testing (EPT). Treatment outcome measures included postoperative symptoms, tooth function, radiographic healing, and recovery of pulp sensibility. Results. All treated teeth (6/6) remained asymptomatic and functional throughout the 12-month follow-up period, with no postoperative complications, such as pain, swelling, sinus tract formation, or abnormal mobility. Progressive recovery of pulp sensibility was observed during follow-up, and positive EPT responses (reflecting neural responsiveness) were detected in two cases at 4 months, one case at 6 months, and in all cases by the 12-month evaluation. CBCT analysis at 12 months demonstrated complete resolution of periapical radiolucency and restoration of apical bone architecture in all treated teeth (6/6). Conclusion. Within the limitations of this pilot clinical study, CGF-enhanced autologous pulp transplantation was associated with favorable short-term clinical and radiographic outcomes, as well as recovery of pulp sensibility in mature necrotic teeth. These preliminary findings suggest the potential of this biologically based regenerative approach. However, comparative effectiveness remains to be established.
Keywords: biological factors; dental pulp; regenerative endodontics; stem cells; transplantation, autologous.